The Effect of Using The Eye Protection Feature on The Incidence Rate of Eye Fatigue (Asthenopia) - Ratih Natasya Maharani; Dea Alya Dirgahayu Pratiwi Dahya; Muh. Alfian Jafar; Marlyanti Nur Rahmah Akib; Hanna Aulia Namira (Ann Publisher, 2026)
Background: The rapid increase in smartphone use among medical students has raised concerns about digital eye strain (asthenopia). Prolonged exposure to blue light from smartphone screens can lead to eye fatigue, including dry eyes, blurred vision, and headaches. Although smartphones are equipped with eye protection features, these are often underutilized. Aim: To examine the effect of smartphone eye protection features on asthenopia among medical students at the Faculty of Medicine, Universitas Muslim Indonesia. Methods: A quasi-experimental pretest–posttest control group study involving 104 medical students evaluated the effect of activating the smartphone eye protection feature on asthenopia using the Visual Fatigue Index, with changes analyzed by the McNemar test (p < 0.05). Results: Prior to intervention, 71 respondents (68.3%) experienced asthenopia, while none used the eye protection feature. After intervention, among the 52 respondents who activated the eye protection feature, 35 (67.3%) showed improvement in asthenopia symptoms, while only 15 (28.8%) continued to experience eye fatigue (p < 0.001). Conversely, in the control group (n=52), 29 respondents (55.8%) who initially had no symptoms developed asthenopia, demonstrating a significant worsening of eye health (p < 0.001). The findings indicate a statistically significant reduction in asthenopia incidence among users of the eye protection feature. Conclusions: The use of smartphone eye protection features significantly reduces the incidence and severity of asthenopia among medical students with prolonged smartphone use. By filtering blue light, this feature improves visual comfort and serves as an effective and practical preventive measure against digital eye strain.